Board Gender Diversity and Firm Performance: Evidence from Family-Owned Firms in India - Rupjyoti Saha; Santi Gopal Maji (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study investigates the impact of board gender diversity (BGD) on firm performance (FP) for family-owned Indian firms. To do so, this study selects a sample of the 75 top-listed family-owned firms for a period of 5 years. For empirical analysis, the study used appropriate panel data models. For robustness, the three-stage least square (3SLS) model was used. The findings obtained from panel data models reveal a significant positive impact of BGD in terms of its different measures on FP after controlling corporate governance and firm-specific characteristics. Such results are further substantiated through the 3SLS model. This study provides novel evidence on the impact of BGD in terms of its diverse constructive measures on FP for family-owned firms in the Indian context, thereby extending the ongoing debate about the outcomes of the mandatory gender quota on board for an emerging market.